Musical expeditions of the Venda - Blacking, John (International Library of African Music, 1962)
The Venda tribe, who live in the Northern Transvaal on the middle Limpopo River, mostly on the south bank in the region north of Louis Trichardt, are noted for their Reed-flute ensembles. Professor Kirby has given us a detailed description of them. The ensemble consists of a set of from nineteen to twenty-six stopped bamboo pipes: they are end-blown, and as each produces only one note, a separate player is needed for every pipe. The pipes are each tuned to a different pitch and together yield a heptatonic scale covering from about two-and-a-half to three-and-a-half octaves, according to the number of pipes in the set.
Keywords: Folk dancing; South Africa; Ethnomusicology; Music; Venda (African people); Venda Dance; Social Life; Social Customs; African Music